Effect of velocity in erosion corrosion - Mohd Khairul Na'im, Mohd Ariffin (2012)
The present study has been conducted to investigate the interaction effect of velocity on erosion corrosion of material in aqueous slurries. Tests were performed on stainless steel samples of grade 301. Pure erosion and pure corrosion as well as erosion corrosion impingement tests were carried out at two different impact velocities 500 rpm, 1000 rpm and also without any velocity. The erosion corrosion test was carried out by immersing the specimen in an aqueous 3.5% NaCl solution and presence of sand particles. Electrochemical Erosion Corrosion Test have been conducted and reported in this thesis. The data then analyze using Ivman software to determine the value of corrosion rate. The surface image and surface roughness value was taken before and after the Electrochemical Erosion-Corrosion test. From observation of the result, when the value of velocity increases the corrosion rate also increases. Besides that, the value of surface roughness also increase when the corrosion rate increase due to present of pitting corrosion.